Skill Complementarity in Production Technology: New Empirical Evidence and Implications - Andrey Stoyanov; Nick Zubanov (Institute of Labor Economics (IZA), 2019)
Matched worker-firm data from Danish manufacturing reveal that 1) industries differ in within-firm worker skill dispersion, and 2) the correlation between within-firm skill dispersion and productivity is positive in industries with higher average skill dispersion. We argue that these patterns are a manifestation of technological differences across industries: firms in the "skill complementarity" industries profit from hiring workers of similar skill level, whereas firms in the "skill substitutability" industries benefit from hiring workers of different skill levels. An empirical method we devise produces a robust classification of industries into the distinct complementarity and substitutability groups. Our study unveils hitherto unnoticed technological heterogeneity between industries within the same economy, and demonstrates its importance. Specifically, we show through simulations on a simple general equilibrium model that failing to take technological heterogeneity into account results in large prediction errors.
Keywords: D24; D58; J2; 330; skill dispersion; complementarity; production technology; firm productivity